Financial tool of liquidity management of commercial banks the national economy of Ukraine - Khalatur, Svetlana; Халатур, Світлана Миколаївна; Bilych, N.; Білич, Н. С. (Інститут підготовки кадрів державної служби зайнятості України, 2018)
Problems with liquidity in banks can lead to a reduction in the solvency of a commercial bank, which in turn results in the infiltration of other banks, resulting in a general loss of confidence in the banking system. Otherwise, solvent banks will suffer great losses as they struggle to mobilize less liquid assets to meet liquidity risk. These losses can quickly undermine the position of capital still weakly capitalized banks. The lack of the possibility of returning reserves and other illiquid banking requirements will force banks to write down these statements unreliable, which leads to significant losses and capitalization. Therefore, the study designed to determine the liquidity risk is an endogenous factor that determines the solvency of the bank and ascertains the attitude and the level of materiality of banking specific variables and variables of macroeconomics with the level of risk of liquidity and solvency of commercial banks. After analyzing, it came to the conclusion that liquidity and solvency management is one of the most important tasks of managing a bank. Thus, in case of a general crisis due to internal or external political changes, seasonal effects, economic cycles, management will most likely assess the impact of these trends and events on the financing of banks. Healthy financial management can counteract negative changes and emphasize positive. The risk of the interaction of liquidity and solvency, as a rule, leads to systemic crises. Effective management of liquidity of commercial banks is crucial in the process of regulating financial payments, implementing international compliance and technological innovation practices that ensure the security of banking activities, capital security and strategic success of the financial industry as a whole. Large-scale modernization of national banking, growth of labor productivity, strengthening of competitive positions of domestic producers is possible on the basis of wide application of investment and innovation model of development. Among the measures to mitigate the negative effects, the main place should be state support. Проблеми з ліквідністю в банків можуть призвести до зниження платоспроможності комерційного банку, а це в свою чергу до зараження інших банків, в результаті чого загальної втрати довіри до банківської системи. В іншому випадку платоспроможні банки зазнають великих втрат, так як вони борються, щоб мобілізувати менш ліквідні активи для задоволення ризику ліквідності. Ці втрати можуть швидко підірвати позиції капіталу як і раніше слабо капіталізованих банків. Відсутність можливості повернення резервів та інших неліквідних банківських вимог змусить банки записати ці твердження безнадійні, що призводить до значних втрат і капіталізації. Тому дослідження призначене для визначення ризику ліквідності є ендогенним фактором, що визначає платоспроможність банку та з'ясовує ставлення і рівень суттєвості банківських конкретних змінних та змінних макроекономіки з рівнем ризику ліквідності і платоспроможності комерційних банків. Після аналізу прийшли до висновку, що управління ліквідністю та платоспроможністю є однією з найбільш важливих завдань управління банком. Таким чином, у разі загальної кризи через внутрішні або зовнішні політичні зміни, сезонні ефекти, економічні цикли, управління буде швидше за все оцінити вплив цих тенденцій і подій на фінансування банків. Здорове фінансове управління може протидіяти негативним змінам і підкреслити позитивні. Ризик взаємодії ліквідності та платоспроможності, як правило, призводить до системних криз. Ефективне управління ліквідністю комерційних банків є вирішальним у процесі регулювання фінансових платежів, реалізації міжнародної відповідності та технологічної інноваційної практики, що забезпечує безпеку банківської діяльності, безпеку капіталу та стратегічний успіх розвитку фінансової галузі в цілому. Масштабна модернізація національного банківництва, зростання продуктивності праці, зміцнення конкурентних позицій вітчизняних виробників можливо на основі широкого застосування інвестиційно-інноваційної моделі розвитку. Серед заходів щодо пом'якшення негативних наслідків, основне місце повинно належати державній підтримці
Фінансові важелі управління ліквідністю комерційних банків у національній економіці України
Keywords: commercial bank; комерційний банк; financial condition; фінансовий стан; liquidity; ліквідність; solvency; платоспроможність; borrowers; позичальники